Spatiotemporal Patterns of Substance P-Bound MRGPRX2 Reveal a Novel Connection Between Macropinosome Resolution and Secretory Granule Regeneration in Mast Cells - Lazki-Hagenbach, Pia; Kleeblatt, Elisabeth; Ali, Hydar; Sagi-Eisenberg, Ronit (Frontiers in Immunology, 2022)
MRGPRX2, the human member of the MAS-related G protein coupled receptors (Mrgprs), serves as the cellular target of human mast cells (MCs) for innate ligands, including neuropeptides and antimicrobial peptides. In addition, MRGPRX2 also functions as the receptor of multiple FDA-approved drugs. As such, MRGPRX2 is a mediator of MC responses in neurogenic inflammation, host defense and pseudoallergy. We analyzed the spatiotemporal patterns of MRGPRX2 following its binding of the neuropeptide substance P (SP). Herein, we show that MRGPRX2 internalizes via both endocytosis and macropinocytosis, followed by its distribution between a perinuclear region and the secretory granules (SGs). Further, we show that MRGPRX2-containing macropinosomes undergo resolution by a mechanism that involves dynamin and LC3, giving rise to the incorporation of both LC3 and MRGPRX2 into the SGs. SP then promotes the acidification of the LC3-associated SGs, presumably by stimulating their fusion with lysosomes. Taken together, our results reveal a unique mode of MRGPRX2 trafficking that complements endocytosis and involves macropinocytosis, autophagic machinery-assisted macropinosome resolution and receptor delivery to the SGs.